2022
DOI: 10.25122/jml-2021-0318
|View full text |Cite
|
Sign up to set email alerts
|

Anterior accessory great saphenous vein as a cause of postoperative recurrence of veins after radiofrequency ablation

Abstract: There are problems of postoperative relapse of veins after radiofrequency ablation (RFA). The study aims to analyze the causes of postoperative recurrence of veins after RFA. 928 patients with varicose veins of the lower extremities, clinical classes C2-C4 according to the CEAP classification, were treated in the ambulatory surgery centers using RFA. The causes of varicose recurrence showed that it was caused by: a) high fusion of the anterior accessory great saphenous vein (AAGSV) with great saphenous vein (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Their study reported a higher rate of recurrent varicose veins in patients who had saphenofemoral junctional, and GSV reflux on ultrasound, and a direct confluence of the AAGSV at the saphenofemoral junction was found to be a negative predictor for recurre varicos veins [12]. Yriji et al [1] reported that the frequency of isolated reflux in the AAGSV was much higher than described in previous literature [13,14,15].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Their study reported a higher rate of recurrent varicose veins in patients who had saphenofemoral junctional, and GSV reflux on ultrasound, and a direct confluence of the AAGSV at the saphenofemoral junction was found to be a negative predictor for recurre varicos veins [12]. Yriji et al [1] reported that the frequency of isolated reflux in the AAGSV was much higher than described in previous literature [13,14,15].…”
Section: Discussionmentioning
confidence: 91%
“…The anterior accessory great saphenous vein (AAGSV) can be defined as any vein that accompanies the great saphenous vein (GSV), lies superficial to GSV on the anterior surface of the thigh, and is not surrounded by the saphenous fascial sheath [1]. An anterior accessory of the great saphenous vein (AAGSV) originates from the marginal veins anterior to the GSV and travels anteriorly to the main trunk in the leg to drain either into the great saphenous vein (in the leg, thigh, or groin) or to drain into the posterior accessory saphenous vein in the leg or thigh [2].…”
Section: Introductionmentioning
confidence: 99%
“… 4 In most studies, ASV reflux is present in about 10% to 20% of patients presenting for treatment and approximately a third of patients present after prior treatment. 4 8 There is an increasing appreciation that addressing ASV reflux is important not only in achieving optimal outcomes in first time treatment patients in the short term but also in addressing the risk of recurrence after treatment in the long-term.…”
Section: Introductionmentioning
confidence: 99%
“…1 Anterior saphenous vein (ASV) reflux is the next most common source of superficial reflux in up to 22% of patients presenting for first time treatment and approximately a third of patients presenting after prior varicose vein treatment. [1][2][3][4][5] In the past, there has been a debate about whether the ASV is simply an accessory vein of the GSV or a defined truncal saphenous vein with a distinct natural history that requires different treatment considerations than a tributary. It is now understood that anatomically the ASV is a truncal saphenous vein with its own proper fascial compartment that is distinct from the GSV.…”
Section: Introductionmentioning
confidence: 99%